Co-occurring mental disorder and intellectual disability in a large sample of Australian prisoners. (October 2013) - Dias, Shannon; Ware, Robert S; Kinner, Stuart A; Lennox, Nicholas G
Objective: Prisoners with intellectual disability who have a coexisting mental health issue often have unmet health needs and are more likely to reoffend than those with intellectual disability alone. The aims of this study were to estimate the prevalence of co-occurring mental disorder among prisoners with intellectual disability and to explore the association between intellectual disability and mental disorder. Methods: Cross-sectional study of adult prisoners within 6 weeks of release from custody in seven prisons in Queensland, Australia between August 2008 and July 2010. Intellectual disability was assessed using a practical composite screening tool. Prisoners who scored <85 on the Hayes Ability Screening Index and reported either having attended a special school or having been diagnosed with intellectual disability were identified as having an intellectual disability. Mental health was assessed using self-reported psychiatric diagnoses, the Kessler Psychological Distress Scale (K-10), and the Mental Component Summary score of the Short-Form-36 health survey version 2. The association between intellectual disability and mental health was assessed using univariate and multivariate logistic regression. Results: Overall, 1279 prisoners completed the HASI: 316 (24%) scored below the recommended cut off for further diagnostic assessment of intellectual disability, 181 (14%) reported attending a special school, and 56 (4%) reported that they had been diagnosed with an intellectual disability. On our composite measure, 115 (9%) participants were identified as having an intellectual disability. Among prisoners with intellectual disability, the estimated lifetime and current prevalence of co-occurring mental disorders was 52.5% (95% CI 43.3–61.5) and 37.2% (95% CI 28.8–46.5), respectively. Of those with intellectual disability, 13.5% (95% CI 8.3–21.1) reported very high psychological distress, as measured by the K10. Prisoners with intellectual disability were significantly more likely than their non-disabled peers to report a current diagnosis of depression [adjusted odds ratio (AOR) 1.8, 95% CI 1.1–3.2] or substance dependence (AOR 3.7, 95% CI 1.6–8.4], after adjusting for potentially confounding variables. Prisoners with intellectual disability were also significantly more likely than their non-disabled peers to use antipsychotic medication (AOR 1.7, 95% CI 1.0–2.8). Conclusions: Prisoners with an intellectual disability were more likely than their non-disabled peers to have elevated rates of psychiatric comorbidity and unmet treatment needs. There is a need for enhanced collaboration between specialist intellectual disability psychiatric services and mainstream prison mental health services, to ensure coordinated service delivery for this dually disadvantaged group.